Identification of Pseudomonas cichorii (Swingle 1925) Stapp 1928 in hydroponic lettuce production - S. Tesic; E. N. Pakina; A. N. Ignatov (Овощи России)
Relevance. Lettuce (Latin: Lactúca satíva) is a species of annual herbaceous plant in the genus Lettuce of the Asteraceae family. As a vegetable crop, it is cultivated everywhere in the world, and its hydroponic cultivation technology has received special development in recent years. One of the common pathogens of lettuce is Pseudomonas cichorii, causing bacterial diseases of several important cultivated plants. In this regard, the study of the occurrence of this pathogen is important.Material and methodology. The study was conducted on the basis of the Department of Agrobiotechnology of the ATI of RUDN University. The samples were provided by a commercial manufacturer of lettuce grown on a flow-through hydroponic line under conditions of minimal microbial contamination. The study of phytopathogenic bacteria includes a number of stages: isolation of bacteria on semi-selective culture media and obtaining a pure culture of bacteria; setting a test for pathogenicity (virulence); studying the phenotypic properties of bacteria; determining the taxonomic position of the isolated strains by molecular methods. All studies were conducted in accordance with the standard methods of identification of phytopathogenic bacteria.Results. As a result of the work, the distribution of the species Pseudomonas cichorii in the hydroponic culture of lettuce in the Russian Federation was confirmed. Although, according to the EPPO database, P. cichorii was first described in Russia in 1965 by microbiological methods, but isolated bacteria are not available in microbiological collections to confirm this conclusion with appropriate diagnostic methods. Twelve isolates of P. cichoriiwere studied by a biochemical and phytopathological tests, and four isolates (01, 04, 06, and 12) that showed the greatest aggressiveness on host plants and tobacco leaves were identified by DNA sequencing of the 16S rRNA gene fragment. The obtained DNA fragments showed a high similarity (99-100%) with the sequences of P. cichoriifrom the Genebank. Evaluation of the virulence of the isolated isolates on a number of other cultivated plants, and the uniformity of their biochemical characteristics showed that they represent a group of bacteria specialized in lettuce.